Design and development of advanced BaTiO3/MWCNTs/PVDF multi-layered systems for microwave applications. (15th September 2019) - Cacciotti, Ilaria; Valentini, Manlio; Raio, Michela; Nanni, Francesca
Graphical abstract: Abstract: Development of absorbing materials at microwaves is of great interest in electronic and military applications, tuning their electromagnetic (EM) properties by varying their composition. In this paper, composite films based on polyvinylidene fluoride (PVDF), barium titanate (BaTiO3 ) nanoparticles and/or multiwalled carbon nanotubes (MWCNTs), were prepared. The innovative idea is to use strong dielectric (BaTiO3 ) and conductive (MWCNTs) fillers to tune the complex permittivity of the resulting material at microwaves (8.2–12.4 GHz). Moreover, on the basis of EM characterization, specific compositions were selected to produce multi-layered slabs by film stacking, exploiting the results of a numerical simulation, which provided information about the required compositions and thicknesses, and the order of the different layers. The designed slabs were realised and their properties compared with the simulated ones. It has been demonstrated that it is possible to gain the desired electromagnetic absorbing performance by alternating different compositions to suit a specific EM design.